Needs, Barriers and Facilitators of Adolescents Participating in a Lifestyle Promotion Program in Oncology: Stakeholders, Adolescents and Parents' Perspective - Johanne Kerba; Catherine Demers; Véronique Bélanger; Mélanie Napartuk; Isabelle Bouchard; Caroline Meloche; Sophia Morel; Nicolas Prud'homme; Isabelle Gélinas; Johanne Higgins; Daniel Curnier; Serge Sultan; et al. (MDPI AG, 2022)
Treatments for adolescent cancer can cause debilitating side effects in the short- and long-term such as nausea and malnutrition but also cardiometabolic disturbances. Although the risk for cardiometabolic complications is greater for adolescents with cancer than younger ones, adolescents typically respond poorly to family-oriented health promotion programs. This study aims to assess the needs, barriers and facilitators to healthy lifestyle promotion interventions for adolescents with cancer and how to best adapt these interventions for them. Interviews were held with adolescents treated for cancer (n = 9) and parents (n = 6), focus groups were conducted with stakeholders working in oncology (n = 12) and self-report questionnaires were sent to stakeholders involved in a health promotion intervention (n = 6). At the time of interview, mean age of adolescent participants (40% female) was 17.0 ± 1.9 years (mean age at diagnosis: 14.6 ± 1.6 years). Verbatim and responses to questionnaires were coded and analyzed using qualitative methods. Stakeholder stated that adolescents with cancer need to access activities adapted to their age, to communicate with peers going through a similar experience, and to preserve their schooling and friendships. Barriers to intervention reported by adolescents, parents and stakeholders include lack of motivation, schedule conflicts, fatigue and treatment side effects. Some of the barriers mentioned by adolescents and parents include pain, post-surgery problems, school, physical deconditioning, and lack of time. Facilitators mentioned by adolescents and parents comprise trust in stakeholders' expertise, personalized approaches, scheduling flexibility. Stakeholders recommended to build trust in the relationship, favoring non-moralizing teachings, adapt interventions to adolescents' limited attention span and avoiding the use of long-term health benefits as a motivator.